Risk factors and a predictive model for acute hepatic failure after transcatheter arterial chemoembolization in patients with hepatocellular carcinoma. (7th January 2013) - Min, Yang Won; Kim, Jeong; Kim, Seonwoo; Sung, Young Kyung; Lee, Jin Hee; Gwak, Geum‐Youn; Paik, Yong Han; Choi, Moon Seok; Koh, Kwang Cheol; Paik, Seung Woon; Yoo, Byung Chul; Lee, Joon Hyeok
Abstract Background/Aims Acute hepatic failure (AHF) is one of the most serious complications of transcatheter arterial chemoembolization (TACE). The aims of this study were to investigate risk factors of AHF after TACE and to establish a predictive model for AHF. Methods In the evaluation set, a total of 820 patients who underwent TACE as a first treatment for hepatocellular carcinoma were included. The demographic, laboratory, radiological and treatment‐related factors were analysed to identify risk factors for AHF after TACE and a predictive model was established using the identified risk factors. In the validation set, a different cohort of 438 patients was included to validate the predictive model. Results The incidence of post‐TACE AHF was 15.1% (124/820). Multivariate analysis revealed that presence of portal vein thrombosis, high aspartate aminotransferase, bilirubin, and log alpha‐foetoprotein levels, and low albumin and sodium levels were independent risk factors. A mathematical model was established using these independent risk factors, and the area under the receiver operating characteristic curve of the model was 0.773 (95% confidence interval, 0.726–0.820). The cut‐off value of 9 had a sensitivity of 78.2%, a specificity of 72.3%, a positive likelihood ratio of 2.82, a negative likelihood ratio of 0.30, a positive predictive value of 28.9% and a negative predictive value of 95.8%. Conclusions The risk factors of post‐TACE AHF were presence of portal vein thrombosis, high aspartate aminotransferase, bilirubin, and alpha‐foetoprotein levels, and low serum albumin and sodium levels. A mathematical model to predict post‐TACE AHF was established.